No Consistent Shift in Leaf Dry Mass per Area Across the Cretaceous—Paleogene Boundary - Butrim, Matthew J.; Royer, Dana L.; Miller, Ian M.; Dechesne, Marieke; Neu-Yagle, Nicole; Lyson, Tyler R.; Johnson, Kirk R.; Barclay, Richard S. (Frontiers in Plant Science, 2022)
The Chixculub bolide impact has been linked to a mass extinction of plants at the Cretaceous—Paleogene boundary (KPB; ~66 Ma), but how this extinction affected plant ecological strategies remains understudied. Previous work indicates that in the Williston Basin, North Dakota, plants pursuing strategies with a slow return-on-investment of nutrients abruptly vanished after the KPB, consistent with a hypothesis of selection against evergreen species during the globally cold and dark impact winter that followed the bolide impact. To test whether this was a widespread pattern we studied 1303 fossil leaves from KPB-spanning sediments in the Denver Basin, Colorado. We used the relationship between petiole width and leaf mass to estimate leaf dry mass per area (LMA), a leaf functional trait negatively correlated with rate of return-on-investment. We found no evidence for a shift in this leaf-economic trait across the KPB: LMA remained consistent in both its median and overall distribution from ~67-65 Ma. However, we did find spatio-temporal patterns in LMA, where fossil localities with low LMA occurred more frequently near the western margin of the basin. These western margin localities are proximal to the Colorado Front Range of the Rocky Mountains, where an orographically driven high precipitation regime is thought to have developed during the early Paleocene. Among these western Denver Basin localities, LMA and estimated mean annual precipitation were inversely correlated, a pattern consistent with observations of both fossil and extant plants. In the Denver Basin, local environmental conditions over time appeared to play a larger role in determining viable leaf-economic strategies than any potential global signal associated with the Chicxulub bolide impact.